Wolffia papulifera Thomps. And W. columbiana Karsten-two New Plant Records for India - Kax, A. Majeed; Bakaya (Kachboo), Usha; Javeid, G. N. (Indian Forester, 1978)
Two new species of Wolffia Horkel, Wolffia papulifera Thomps. and W. columbiana Karsten have been collected from the Kashmir valley. The species have not been reported sofar in the extent literature from the Indian subcontinent. The species, in the present forum, are described and illustrated.Î½